THE ROLE OF LOCAL COMMUNITY ORGANIZATIONS IN SUPPORTING TOURISM VILLAGES (A STUDY IN PASSIMARANNU VILLAGE, SINJAI REGENCY, MARANNA BEACH TOURIST ATTRACTION) - Andi Qaisar (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2025)
ABSTRACT This study examines the role of local community organizations in the development of Passimaranu Tourism Village in Sinjai Regency, Indonesia. Building on a community-based tourism framework, the study explores how organizations such as Pokdarwis mobilize local resources, preserve cultural heritage, and promote sustainable tourism practices. Using a qualitative approach through observation, interviews, and document analysis, the research findings reveal that these organizations serve as key facilitators in managing tourism activities, coordinating stakeholder collaboration, and ensuring inclusive community participation. The results of the author's literature review indicate that local institutions play a significant role in the tourism sector. These institutions can increase community participation in tourist villages, develop the local economy, and foster sustainable social development. The author's recommendation is that local institutions can enhance their efforts by collaborating with the government to develop infrastructure, promote tourism practices internationally, and expand tourism education in secondary schools. Keywords: Local Communities, Tourism Villages